2015
DOI: 10.17831/enq:arcc.v12i1.392
|View full text |Cite
|
Sign up to set email alerts
|

Luminous Color in Architecture: Exploring Methodologies for Design-Relevant Research

Abstract: This paper describes our process in conducting research toward better understanding of the experience and perception of luminous colors in architectural contexts. Our intention is to contribute to a body of knowledge useful for designers by introducing a designerly way of working into an otherwise academic research approach. Luminous color influences our perception of form, space, and ambiance. The use of such color in architectural design has increased significantly over the past two decades, and with the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This study found that within color attributes, value contrast, which has a strong correlation with illumination, was the most significant factor influencing visual comfort. This reaffirms that the primary determinant of visual comfort is lighting conditions [27,52], and individuals' perception of spatial environments is largely influenced by the interplay between light and color [53]. This outcome may be attributable to the fact that visual discomfort is related to specific times of the day and certain weather conditions [54].…”
Section: Effects Of Luminance Contrast (Vc) and Chromaticity Contrast...supporting
confidence: 60%
“…This study found that within color attributes, value contrast, which has a strong correlation with illumination, was the most significant factor influencing visual comfort. This reaffirms that the primary determinant of visual comfort is lighting conditions [27,52], and individuals' perception of spatial environments is largely influenced by the interplay between light and color [53]. This outcome may be attributable to the fact that visual discomfort is related to specific times of the day and certain weather conditions [54].…”
Section: Effects Of Luminance Contrast (Vc) and Chromaticity Contrast...supporting
confidence: 60%
“…Thanks to the evolution of the control systems used in the field of cinematography, together with the possibilities offered by LED technology, the implementation and development of the DMX protocol as a control system applied to the field of architectural lighting is a credible fact. This control system offers the opportunity for a new understanding of lighting based on the promotion of qualitative, dynamic, and versatile aspects [21,22].…”
Section: Discussionmentioning
confidence: 99%